Phytoestrogen Activity of Alkaloid Compounds of Butterfly Pea (Clitoria ternatea) Using In Silico Analysis - Fitriyah, Fitriyah; Ramadhani, Anggia Noor (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2024)
Estrogen is a hormone that plays a role in sexual and reproductive development, especially in women. Estrogen is not only important for reproduction, but also in other systems such as the cardiovascular system, neuroendocrine system, immune system and muscoskeletal system in men and women. The absence of estrogen during the menopause phase is a leading factor in the onset of cardiovascular disease. Phytoestrogens are polyphenolic and non-steroidal compounds that have a structure and biological activity similar to 17β-estradiol in humans. Most phytoestrogens are found in flavonoids, isoflavones and also alkaloids whose esterogenic potential has not been widely explored. Butterfly Pea (Clitoria ternatea) is a type of wild creeping plant from the Fabaceae family which contains a number of active ingredients, including alkaloids. This research aims to determine the active compounds derived from Butterfly Pea (Clitoria ternatea) alkaloids which have the best potential as phytoestrogens using the insilico method. A number of ligands which are active compounds derived from alkaloids in Butterfly Pea are linked to estrogen alpha as a receptor using molecular docking. The research results of the six alkaloid derivative compounds found in the leaves, flowers and seeds tested showed that Cephalotaxinone was the most effective compound to be used as a phytoestrogen candidate